Virtual relationships: the dancer and the avatar. Issue 1 (3rd April 2021) - Strutt, Dan; Cisneros, Rosa
ABSTRACT: People might assume that dancing with a digital avatar would be a relatively distant, dehumanizing or disembodied process. However, in this article we propose that effective and creative choreographic practice can be achieved by working with a virtual representation of a dancer, and we offer two case studies to evidence the practical application of motion capture technology within this context. We observed that the virtual model quickly and naturally becomes an extension of the dancer's interiority and that a dynamic affective attunement between dancer and avatar spontaneously develops. We describe how the relationship between the physical and the virtual dancing body raises several practical, theoretical and even philosophical questions for choreographic approach, style and process. Building from Susanne Langer's (1953) germinal conception of the 'virtual powers' of dance, we articulate a practice-led research opportunity to critically reflect on conventional choreographic practices through the affordances of a specifically digital virtuality, in ways that can open out the kinds of affective, emotional and phenomenological frameworks within which creation occurs. The unique affordances of recent motion capture systems, offer naturalistic three-dimensional environments with an increased improvisational interactivity that simply cannot be achieved with video-based media.